Banking sector depth & long-term economic growth in the GCC States: relationship nature, sector development status & policy implications - Al-Moulani, Ali J. (Cranfield University, 2016)
The thesis investigates the nature of the relationship between the banking sector depth and long-term economic growth in the Gulf Cooperation Council (GCC) States, assesses the banking sector development status in each of the States, and underlines the policy implications in the light of the banking-growth nexus and the banking development benchmarking models’ findings for the region by undertaking three projects. The thesis examines the nature of the relationship between banking sector depth and long-term economic growth in the NRBC—as a proxy for the GCC States— vis-à-vis the rest of the world countries. For the empirical investigation, a dynamic panel data approach, i.e. Generalised Method of Moments (GMM), is adopted over the period 1961 to 2013. By utilising mixed effects and System GMM frameworks, the research identifies the countries with the strongest banking-growth relationships and establishes the banking sector development determinants in those countries. Employing a novel benchmarking process, the thesis assesses the status of the banking sector development in each of the GCC member countries and simulates the change in the banking sector depth across the Gulf region over a period of ten years to highlight the potential policy implications for the sector development. The findings of the thesis suggest that the relationship between banking sector depth and long-term economic growth in the NRBC is non-linear, where the relationship between the banking sector depth and economic growth turns from positive to negative beyond certain levels of sector depth. In comparison to other countries, the results indicate that the banking-growth nexus in the NRBC exhibits a smaller total effect magnitude as well as a shorter time between the change in the sector depth and its effect on economic growth. The benchmarking of the banking sectors in the GCC region suggests that in five of the six member countries the banking sectors are underdeveloped. The simulation results predict that the banking sectors will develop further in half of the countries in the region, given their current levels of banking sector development determinants, while two countries require reforms in terms of undertaking regulations and policies to avoid seeing their sector development levels deteriorate. The thesis contributes to theory by confirming findings in the literature and expanding the body of knowledge through novel findings. This research also contributes to policy by demonstrating the significance of the banking sector development for long-term economic growth in the NRBC, providing policymakers in the Gulf States with the status of their banking sectors, and underlining the banking sector depth determinants that ought to be considered when setting regulations and policies that are aimed at developing the banking sector further.
Keywords: Finance-Growth Nexus; Banking Sector Development Benchmarking; Banking Depth Determinants; Natural Resource-Based Countries; Generalised Method of Moments